A comparative study of fatigue estimation methods for single‐spot and multispot welds. Issue 6 (25th January 2020) - Yang, Long; Yang, Bing; Yang, Guangwu; Xiao, Shoune; Zhu, Tao; Wang, Feng
Abstract: Fatigue life and load data of spot‐welded samples were obtained by performing tensile‐shear fatigue tests on single‐spot‐welded samples, and by collecting published data on tensile‐shear fatigue tests of multispot‐welded samples. Finite element models of the spot‐welded samples were then constructed, and their accuracy was validated by comparing their results with those of static loading tests. Methods to estimate fatigue in spot‐welded joints proposed by Sheppard, Rupp, and Swellam were used to predict the fatigue life of each sample, and their results were compared. The sensitivity of each method to spot‐welding parameters, as well as the arrangement and number of welded spots, was analyzed to obtain their scope of applicability. Finally, the Sheppard and Rupp methods were used to obtain fitted fatigue curves of each spot‐welded sample, and the equivalent life method was used to generate P‐S‐N curves of the single‐spot‐ and multispot‐welded samples. This method can serve as a useful reference for fatigue reliability analyses of mechanical parts with spot‐welded joints.